A panel of polymorphic bovine, ovine and caprine microsatellite markers - Kemp, Stephen J.; Hishida, O; Wambugu, J.; Rink, A.; Longeri, M.L.; Ma, R.Z.; Da, Y.; Lewin, H.A.; Barendse, W.; Teale, A.J. (Wiley, 1995)
A panel of 81 new polymorphic bovine microsatellite markers is described, together with further information on a previously reported group of 16 markers. The mean polymorphism information content of the 97 markers determined in 20 cattle was 0.66. Seventy-three of these markers have been assigned to chromosomes by either linkage analysis or use of hybrid cell panels. Thirty-nine of the markers were polymorphic in sheep, and 32 were polymorphic in goat. This study identified a set of 18 robust markers that were polymorphic in all three species and that covered 14 bovine chromosomes. This provides a single group of markers, which would be suited to genetic distance analysis and parentage control in cattle, sheep and goat.